Coins Unearthed in the Virgin Mary Church in Zeytinliada - Murat, Mehmet Kayhan (Fırat Üniversitesi, 2023)
Zeytinliada is located 250 m offshore of Erdek District of Balikesir Province in the Sea of Marmara. The excavations on the island, known as Artake and Arteceon in Antiquity, started in 2006 and were completed in 2016. The Church of the Virgin Mary, located in the northeast of the island, was unearthed during the excavations carried out in 2006-2009. The church, dating to the Early Byzantine Period, has a basilica plan with 3 naves. In this study, 44 coins, among the small finds unearthed during the excavations in the church, were examined. Of the 44 coins found in the church, 36 were identified, and 8 could not be identified due to excessive deterioration. The coins described belong to the Roman, Byzantine and Ottoman Empire Periods. Coins were minted during the dynastic years of 10 different emperors. The coins found in the Virgin Mary Church in Zeytinliada belong to 4 different mints and are in 7 different units. The earliest dated coins belong to AD 276-282, and the latest dated 1861. The majority of the coins are Byzantine coins, which are contemporary with the church, with 32 coins. 16 Byzantine coins are dated to the Early Byzantine Period and 2 Middle Byzantine Period. The coins we examined provide important information about the dating of the building and the coin circulation of the period.

Zeytinliada, Marmara Denizi’nde Balıkesir İli’nin Erdek İlçesi’nin 250 m açıklarında yer almaktadır. Antik Dönem’de Artake ve Arteceon adlarıyla anılan adadaki kazılara 2006 yılında başlanıp 2016 yılında bitirilmiştir. Adanın kuzeydoğusunda yer alan Meryem Ana Kilisesi 2006-2009 yıllarında yapılan kazılarda açığa çıkarılmıştır. Erken Bizans Dönemi’ne tarihlenen kilise 3 nefli bazilikal bir plana sahiptir. Bu çalışmada kilisedeki kazılarda ele geçen küçük buluntular arasında yer alan 44 sikke incelenmiştir. Kilisede ele geçen 44 sikkeden 36’sı tanımlanmış, 8 sikke uğradıkları aşırı bozulmadan dolayı tanımlanamamıştır. Tanımlanan sikkeler Roma, Bizans ve Osmanlı İmparatorluğu Dönemleri’ne aittir. Sikkeler 10 farklı imparatorun hanedanlık yıllarında darp edilmiştir. Zeytinliada Meryem Ana Kilisesi’nde ele geçen sikkeler 4 ayrı darphaneye ait olup 7 farklı birimdedir. İncelenen sikkelerden en erken tarihlisi MS 276-282, en geç tarihlisi 1861 yıllarına aittir. Sikkelerin genel çoğunluğunu 32 sikkeyle kilise ile çağdaş olan Bizans sikkeleri oluşturmaktadır. Bizans sikkelerinden 16 tanesi Erken Bizans Dönemi’ne, 2 tanesi Orta Bizans Dönemi’ne tarihlenmektedir. İncelediğimiz sikkeler yapının tarihlendirilmesi ve dönemin sikke dolaşımı hakkında önemli bilgiler vermektedir.
ZEYTİNLİADA MERYEM ANA KİLİSESİ’NDE ELE GEÇEN SİKKELER